(3GdSjQI hCNHGQ GdCeI (B( (3aj GfJTGQ ePgH GdEHGVjI aj GdeZQH (B)s - (3jMji Hf CHj HcQ GdhQLdGfj, CHh RcQjG,J (B471 (3g` s ((3EHQGgje Hf SdjeGf GdTeGNi GdHbhSi s)
(3ChdgG (B:s
(3CeG HYO , aEfg QCjfG eG CfWeS ef GdBKGQ GfHYKJ CacGQfG Edi JCdja GNHGQ eG Sda ef eTGjN Cgd GdOYhI hUdMGFgG s
(3BNQgG (B:s
(3hPcQ CHh GdQHjY Cf CHG YHO Gddg eMeO Hf QVi Gddg Yfg bGd (B: (3dGJbhe GdSGYI bdjdjb s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B139 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B188s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B336 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B242 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs